Generalized microdontia and associated anomalies: A clinical, genetic, radiological and dermatoglyphic study - (:unkn) unknown (My University, 1996)
The clinical, genetic, radiological and dermatoglyphic findings of a case showing generalized microdontia associated with an extra maxillary central incisor, hypoplastic maxilla, prognathic mandible, wide-sets of the ears, hooked nose, astigmatism, camptodactyly, flexion contractures of the distal interphalangeal joints of the fingers, thinning of the fingers towards the distal end of the palm, and complete webbing of the IVth and Vth toes (syndactyly type III) and short stature were presented.